Relationship of Gratitude with Optimistic Life Orientation among University Teachers - Hafsa Ghafoor; Sana Bibi; Inayat Shah; Kainat Zia (Journal of Management Practices, Humanities and Social Sciences, 2024)
The present study sought to investigate the influence of gratitude on optimistic mindsets among university teachers in Lower Dir, Pakistan. The study used a correlational research approach and readily selected a sample of 150 university lecturers. Participants were administered the Gratitude Questionnaire (GQ6) and the Revised Life Orientation Scale (LOTR). The data analysis was performed using the Statistical Package for Social Science (SPSS-22) software. This involved conducting correlation analysis, t-tests, and descriptive statistics to investigate the demographics, means, standard deviations, and correlation of the variables. The findings revealed a strong and statistically significant positive relationship between gratitude and optimism (r =.374**, p < .01). Gender differences indicated significant mean differences in both study variables. Scores of males and females (M= 34.45, 27.44) and standard deviation (SD = 4.24, 8.15) on GQ6 with t- value (6.94), which indicates males show more gratitude than females. Additionally, significant mean differences between males and females (M 27.27, 29.26) and standard deviation (SD = 5.67, 6.54) on LOTR with t-value (-2.01), which indicates females have a more optimistic orientation of life than males. Marital status revealed no significant score disparities. The results indicate a favorable correlation between gratitude and optimism, unaffected by marital status but major differences in the gender of university teachers.